2020
DOI: 10.1038/s41598-020-75724-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between chronotype and risk of depression

Abstract: Information on sex differences in the association between chronotype and depression is scarce. We aimed to investigate these differences using data from the Korea National Health and Nutrition Examination Survey in 2016. Chronotypes were categorised based on mid-sleep time on free days corrected by sleep debt accumulated on workdays (MSFsc): early type, < mean MSFsc − 1 standard deviation (SD); intermediate type, between mean MSFsc − 1 SD and MSFsc + 1 SD; and late type, > mean MSFsc + 1 SD. A Patient He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…The chronotype can also change with age and appears to be gender-related ( Figure 1 ). In adults, eveningness predominates among males and morningness among females, although the difference disappears in menopause and during old age when early chronotypes are associated with early wake-up timing [ 148 , 149 , 150 , 151 , 152 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chronotype can also change with age and appears to be gender-related ( Figure 1 ). In adults, eveningness predominates among males and morningness among females, although the difference disappears in menopause and during old age when early chronotypes are associated with early wake-up timing [ 148 , 149 , 150 , 151 , 152 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, Kim et al recently reported no difference in prevalence rates for depression in late chronotypes vs. neither types in a population of Korean adults stratified by age (19–40, 41–59 and 60–80 years). However, although the total sample size was large ( N = 6382) the number of participants in the older 60–80 years group classified as evening-type was small ( N = 22) which may limit interoperability 101 . Counter to this, eveningness has been associated with increased odds for reporting depression in a large sample of older adults (age range 40–70 years) taken from the UK Biobank 102 .…”
Section: Discussionmentioning
confidence: 99%
“…The evening chronotype among females has some unfavorable aspects concerning school and work in young and old females ( Fabbian et al, 2016 ). A potential explanation is the gender difference in melatonin, sex hormones, and behavioral and psychological factors (sleep quality, alcohol intake) ( Kim et al, 2020 ). In addition, the circadian gene PER3 variable number of tandem repeats was independently related to chronotype only in males ( Weiss et al, 2020 ).…”
Section: The Differences Between Chronotypes and The Association With...mentioning
confidence: 99%